Apixaban for Patients With Atrial Fibrillation on Hemodialysis: A Multicenter Randomized Controlled Trial. Issue 23 (6th November 2022) - Pokorney, Sean D.; Chertow, Glenn M.; Al-Khalidi, Hussein R.; Gallup, Dianne; Dignacco, Pat; Mussina, Kurt; Bansal, Nisha; Gadegbeku, Crystal A.; Garcia, David A.; Garonzik, Samira; Lopes, Renato D.; Mahaffey, Kenneth W.; et al.
Abstract : Background: There are no randomized data evaluating the safety or efficacy of apixaban for stroke prevention in patients with end-stage kidney disease on hemodialysis and with atrial fibrillation (AF). Methods: The RENAL-AF trial (Renal Hemodialysis Patients Allocated Apixaban Versus Warfarin in Atrial Fibrillation) was a prospective, randomized, open-label, blinded-outcome evaluation (PROBE) of apixaban versus warfarin in patients receiving hemodialysis with AF and a CHA2 DS2 -VASc score ≥2. Patients were randomly assigned 1:1 to 5 mg of apixaban twice daily (2.5 mg twice daily for patients ≥80 years of age, weight ≤60 kg, or both) or dose-adjusted warfarin. The primary outcome was time to major or clinically relevant nonmajor bleeding. Secondary outcomes included stroke, mortality, and apixaban pharmacokinetics. Pharmacokinetic sampling was day 1, day 3, and month 1. Results: From January 2017 through January 2019, 154 patients were randomly assigned to apixaban (n=82) or warfarin (n=72). The trial stopped prematurely because of enrollment challenges. Time in therapeutic range (international normalized ratio, 2.0–3.0) for warfarin-treated patients was 44% (interquartile range, 23%–59%). The 1-year rates for major or clinically relevant nonmajor bleeding were 32% and 26% in apixaban and warfarin groups, respectively (hazard ratio, 1.20 [95% CI, 0.63–2.30]), whereas 1-year rates for stroke or systemic embolism were 3.0% and 3.3% in apixaban and warfarin groups, respectively. Death was the most common major event in the apixaban (21 patients [26%]) and warfarin (13 patients [18%]) arms. The pharmacokinetic substudy enrolled the target 50 patients. Median steady-state 12-hour area under the curve was 2475 ng/mL×h (10th to 90th percentiles, 1342–3285) for 5 mg of apixaban twice daily and 1269 ng/mL×h (10th to 90th percentiles, 615–1946) for 2.5 mg of apixaban twice daily. There was substantial overlap between minimum apixaban blood concentration, 12-hour area under the curve, and maximum apixaban blood concentration for patients with and without a major or clinically relevant nonmajor bleeding event. Conclusions: There was inadequate power to draw any conclusion regarding rates of major or clinically relevant nonmajor bleeding comparing apixaban and warfarin in patients with AF and end-stage kidney disease on hemodialysis. Clinically relevant bleeding events were ≈10-fold more frequent than stroke or systemic embolism among this population on anticoagulation, highlighting the need for future randomized studies evaluating the risks versus benefits of anticoagulation among patients with AF and end-stage kidney disease on hemodialysis. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02942407.